Innovative modes of financing the development of Waqf properties in Malaysia - Mohammad, Mohammad Tahir Sabit (2006)
The institutions of waqf (Majlis Agama Islam) in Malaysia are traditionally seeking finance from government or use their own resources. This limits their capabilities and therefore a need for alternative means of financing is felt. This paper thus proposes a range of financing methods, traditional as well as contemporary in the form credit based modes, joint ventures, securitization, and self-financing. These modes can be practiced by waqf institutions in their development projects by seeking loans (by way of murabahah, istisna and ijarah), financing through risk and profit sharing (i.e. mudrabah and musharaka), securitization of assets (in the form of equity and bond) by institutions, and corporate structuring. This paper also discusses the existing self-financing form of saham waqf and other modes. All these modes presuppose a single project based fiancing and the waqf institutions are ready to grant hikr (long term lease) to its own subsidiary who can sublease the particular parcel of land to the newly formed corporation.